Sustainable operations and the controversy of civet coffee - Maya Irjayanti; Anton Mulyono Azis; Nurul Fatimah (Discover Sustainability)
Abstract This study aims to investigate the operational procedures of civet coffee production and assess its sustainability potential from both a business and animal welfare perspective. This study employs a qualitative methodology, including one focus group discussion (FGD) and 12 in-depth interviews to analyze participants’ experiences, attitudes, and viewpoints regarding civet coffee production. The collected data were examined utilizing open coding and data triangulation methods to ensure the validity of the results. Despite numerous studies emphasizing animal welfare concerns and the negative environmental impacts of civet coffee production, a research gap exists regarding the implementation of more ethical and ecological production procedures without compromising business profitability. This study addresses the gap by offering an examination of the problems and opportunities within the sustainable civet coffee business. The findings supported the data, which indicates that legal civet coffee enterprises in Indonesia adhere to ethical and environmental conservation by examining civet welfare through husbandry criteria in their operation. The findings encourage the adoption of more sustainable and ethical production procedures to enhance customer trust and support the reputation of civet coffee in the worldwide market. This study contributes to enriching the academic discourse on sustainable coffee production practices in line with the sustainable development goals (SDG 12 and SDG 15). These results are anticipated to assist industry stakeholders and policymakers in formulating more transparent and sustainability-focused strategies, enabling the civet coffee business to expand without jeopardizing animal welfare and environmental sustainability.